2016
DOI: 10.1039/c6ay01709f
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensitive monoclonal antibody-based ELISA for the determination of a β-adrenergic agonist brombuterol in swine meat, liver and feed samples

Abstract: A sensitive enzyme-linked immunosorbent assay (ELISA) based on a newly prepared monoclonal antibody (mAb) for the determination of a β-adrenergic agonist brombuterol in swine meat, liver and feed samples was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The qualified rates for beta-agonist residues in China remained lower than the satisfactory level, which is higher than 98%. In addition, many research institutions and universities in China analyzed beta-agonist residues in swine muscle samples collected from local supermarkets, traditional markets, and slaughterhouses [8][9][10][11] and confirmed that clenbuterol, salbutamol, and ractopamine were detected in a few meat samples. Therefore, the strict monitoring and control of beta-agonist residues are still required to meet the regulations in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…The qualified rates for beta-agonist residues in China remained lower than the satisfactory level, which is higher than 98%. In addition, many research institutions and universities in China analyzed beta-agonist residues in swine muscle samples collected from local supermarkets, traditional markets, and slaughterhouses [8][9][10][11] and confirmed that clenbuterol, salbutamol, and ractopamine were detected in a few meat samples. Therefore, the strict monitoring and control of beta-agonist residues are still required to meet the regulations in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the instruments are expensive, and their operation is complicated and requires professional personnel; moreover, these approaches cannot meet the need for rapid, large-scale sample screening and are therefore limited in practical applications. 12 Immunoassays mainly include the enzyme-linked immunosorbent assay (ELISA), 13 , 14 chemiluminescence immunoassay (CLIA) 15 and immunochromatography (ICA). 16 , 17 ELISA has the advantages of high sensitivity and high throughput, but it also presents the disadvantages of a high false positive rate and inability to provide rapid on-site detection.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the enzyme-linked immunosorbent assay (ELISA) has attracted increasing attention for rapid screening as a result of its low cost, simple manipulation and short assay time. [11][12][13][14] Although the traditional ELISA for RAC detection using competitive methods is fast and effective, it still has a high detection limit and produces many false positives. To overcome these drawbacks, we propose a novel immunosensor based on ELISA for the sensitive, low-cost and rapid detection of RAC on-site.…”
Section: Introductionmentioning
confidence: 99%